A novel carboxamide bromodomain inhibitor attenuates osteoarthritis via epigenetic repression of NF-κB and MAPK signaling - Lee, Hyemi; Han, Seong Jae; Ok, Subin; Lee, Kwang Min; Choi, Seungseok; Yoon, Injoo; Choi, Somang; Kim, Jina; Ryu, Serim; Son, Min-Hee; Lee, In-Hyun; Cho, Chanmi; et al. (Frontiers in Immunology, 2025)
Bromodomains are epigenetic readers that modulate gene expression linked to inflammation and cartilage degeneration. Emerging evidence suggests their dysregulation plays a pivotal role in osteoarthritis (OA) pathogenesis, making them promising therapeutic targets. We evaluated the therapeutic efficacy of a novel carboxamide derivative bromodomain inhibitor (NCD) as a potentially safer alternative for preventing OA progression. The inhibitory effects of NCD were assessed through both in vitro and in vivo models. In vitro, mouse primary chondrocytes were stimulated with IL-1β, and the effects of NCD treatment were analyzed using reverse transcription-polymerase chain reaction (RT-PCR) and western blotting. In vivo, destabilization of the medial meniscus (DMM) surgery was performed in 12-week-old male C57BL/6 mice, followed by either oral administration or intra-articular (IA) NCD injection. Cartilage integrity was assessed by histology. We analyzed changes in the NF-κB and mitogen-activated protein kinase (MAPK) signaling pathways to elucidate the mechanism of NCD. NCD treatment significantly suppressed IL-1β-induced expression of matrix metalloproteinases (Mmp3 and Mmp13) and cyclooxygenase-2 (Cox2) in mouse chondrocytes. In the DMM mouse model, both oral IA administration of NCD alleviated OA-related cartilage destruction. Mechanistically, NCD inhibited IκB degradation and reduced Erk and Jnk phosphorylation, indicating suppression of the NF-κB and MAPK signaling pathways. This study demonstrates that targeting bromodomains with a novel carboxamide-based inhibitor effectively attenuates OA cartilage destruction by suppressing these signaling pathways. These findings support the therapeutic potential of epigenetic modulation in mitigating OA pathogenesis.